Implementation of BAZNAS Regulation No. 2/2016 in the Collection of Zakat, Infak and Sadaqah (ZIS) by the Zakat Collector Unit - Tubagus Abdul Fatahillah; Dina Febriani (ALSYS, 2026)
Effective governance of zakat collection requires clear regulatory implementation, institutional coordination, and public literacy, particularly in urban contexts with complex administrative structures. This study examines the implementation of Peraturan Badan Amil Zakat Nasional (Perbaznas) Regulation No. 2 of 2016 concerning the establishment and governance of Zakat Collection Units (UPZ), with a focus on its application within BAZNAS (BAZIS) of DKI Jakarta Province. Using a descriptive qualitative approach and Van Meter and Van Horn’s policy implementation model, the study collected data through in-depth interviews, document analysis, and field observations. The findings indicate that the implementation of the regulation has contributed to increased collection of zakat, infaq, and sadaqah (ZIS), as reflected in the growth recorded in 2023 and 2024. However, policy implementation remains constrained by limited human resource capacity, weak inter-unit coordination, and low zakat literacy among urban communities. Conversely, regulatory support, digitalization, and the active participation of civil servants serve as enabling factors that strengthen the implementation process. The study concludes that the effectiveness of Perbaznas Regulation No. 2 of 2016 depends on institutional capacity, coordinated governance, digital adaptation, and context-sensitive public engagement. These findings contribute to the literature on Islamic public policy and provide practical implications for improving professional, adaptive, and sustainable zakat governance within urban government institutions.